2021
DOI: 10.3389/fpls.2021.778717
|View full text |Cite
|
Sign up to set email alerts
|

Ovary Abortion Induced by Combined Waterlogging and Shading Stress at the Flowering Stage Involves Amino Acids and Flavonoid Metabolism in Maize

Abstract: Maize (Zea mays L.) crops on the North China Plain are often subject to continuous overcast rain at the flowering stage. This causes waterlogging and shading stresses simultaneously and leads to huge yield losses, but the causes of these yield losses remain largely unknown. To explore the factors contributing to yield loss caused by combined waterlogging and shading stress at the flowering stage, we performed phenotypic, physiological, and quasi-targeted metabolomics analyses of maize plants subjected to water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…Soil application of Zn improved maize yield mainly by increasing IG number and weight, but had no such effect on SG [ 13 ]. Improper cropping techniques or ecological stressors can hinder the development of IG or even cause it to fail compared to SG in maize [ 17 , 18 ]. These results imply that IG in maize may be more susceptible to environmental and agronomic changes than SG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil application of Zn improved maize yield mainly by increasing IG number and weight, but had no such effect on SG [ 13 ]. Improper cropping techniques or ecological stressors can hinder the development of IG or even cause it to fail compared to SG in maize [ 17 , 18 ]. These results imply that IG in maize may be more susceptible to environmental and agronomic changes than SG.…”
Section: Discussionmentioning
confidence: 99%
“…This distinction is similar in wheat [ 15 ] and rice [ 16 ]. Inadequate cultivation practices or adverse stresses can further amplify this developmental difference between IG and SG, or even result in IG abortion, ultimately adversely affecting maize yield [ 17 , 18 ]. Consequently, a great deal of research has gone into finding efficient agronomic techniques to improve IG filling and hence increase crop yield.…”
Section: Introductionmentioning
confidence: 99%
“…The biosynthesis and degradation of these amino acids are related to glycolysis/gluconeogenesis or the TCA cycle. ZmCS1 (citrate synthase 1, 100280203) is a key gene involved in the TCA cycle and has been reported the associated with phenylpropanoid hydroxycitric acids, avonoids and benzoxazinoids [10].…”
Section: Discussionmentioning
confidence: 99%
“…Metabolite pro ling studies have revealed that drought stress triggers the production of a diverse range of metabolites in maize. In response to drought, maize undergoes various adaptive reactions, including the synthesis of sugars and free amino acids to regulate osmotic pressure, the activation of anti-oxidative enzymes such as superoxide dismutase (SOD) and catalase (CAT) [8], and the production of antioxidants like glutathione stransferase (GSH-S) [9] and avonoids [10] to counteract reactive oxygen species (ROS) or regulate stomatal opening and closing via ABA hormone signaling [11]. The metabolic pathways of redox homeostasis, osmoregulation, and membrane remodelling play crucial roles in maize drought resistance mechanisms [12].…”
Section: Introductionmentioning
confidence: 99%
“…To capture the metabolomic changes during wheat seed development, quasi-targeted metabolomics was employed to analyze the wheat samples under a contract with Novogene Co., Ltd. (Beijing, China). The metabolomic method was established by Novogene and reported previously 53 55 . The method is described in detail as below.…”
Section: Methodsmentioning
confidence: 99%